The neuroanatomy of asomatognosia and somatoparaphrenia. Issue 3 (24th September 2009) - Feinberg, Todd E; Venneri, Annalena; Simone, Anna Maria; Fan, Yan; Northoff, Georg
Abstract : Objectives: Asomatognosia is broadly defined as unawareness of ownership of one's arm, while somatoparaphrenia is a subtype in which patients also display delusional misidentification and confabulation. Studies differ with regard to the underlying neuroanatomy of these syndromes. Methods: Three groups of patients with right-hemisphere strokes and left hemiplegia were analysed: G1, asomatognosia+neglect; G2, non-asomatognosia+neglect; G3, hemiplegia only. The asomatognosic group was further subdivided into somatoparaphrenia (G1-SP: asomatognosia+delusions/confabulation) and simple asomatognosia (G1-SA; asomatognosia without delusions/confabulation). Results: Patients with all forms of asomatognosia (G1) had larger lesions than non-asomatognosic patients in all sectors. While patients with or without asomatognosia had significant temporoparietal involvement, we found that the subset of patients with somatoparaphrenia had the largest lesions overall, and somatoparaphrenia cases had significantly more frontal involvement than patients with simple asomatognosia. All patients with asomotognosia (G1-SP and G1-SA) had significant medial frontal damage, suggesting that this region may play a role in the development of asomatognosia in general. Somatoparaphrenia cases also had greater orbitofrontal damage than simple asomatognosia cases, suggesting that the orbitofrontal lesion was critical in the development of somatoparaphrenia. Conclusions: Asomatognosia results from large lesions involving multiple—including temporoparietal—sectors, but the addition of medial frontal involvement appears important. The addition of orbitofrontal dysfunction distinguishes somatoparaphrenia from simple asomatognosia. The data indicate roles for the right medial and orbitofrontal regions in confabulation and self-related systems.